Improving Cognitive Learning Outcomes of Grade 3 Elementary School Students Using Labyrinth Learning Media in Social Science Materials - Arinal Haq; Agung Setyawan; Mohd Rushidi Mohd Amin (Sekolah Tinggi Agama Islam Nurul Islam Mojokerto, 2025)
This research aims to improve the cognitive learning outcomes of 3rd grade students of SDN Keleyan 3 in Natural and Social Sciences (IPAS) subjects through the use of game-based maze learning media. The research method used is Classroom Action Research (PTK) with a qualitative approach, carried out in two cycles. Cycle I uses the conventional lecture method, while Cycle II applies labyrinthine media. Data was collected through observation, interviews, questionnaires, and documentation. The results showed a significant increase in students' cognitive learning outcomes from an average of 40.8% in Cycle I to 81.5% in Cycle II. Labyrinth learning media has been shown to be effective in improving cognitive learning outcomes, student understanding, active participation, and learning motivation. These findings confirm the importance of using innovative learning media that are in accordance with the characteristics of elementary school students.